The impact and desirability of news of risk for schizophrenia. - Roni G Alder (Public Library of Science (PLoS), 2013)
In studies of schizotypy, investigators seldom inform participants that they are engaged in research designed to shed light on risk for schizophrenia. Such nondisclosure is justified in part by the argument that disclosure of risk status may be harmful. However, there is little evidence that this is the case. Harm arising from disclosure of risk status was examined in two experiments. In the first, participants (n = 114 psychology undergraduates) were asked to anticipate their reactions to news of risk for schizophrenia, depression, cancer, and diabetes, and also to indicate whether they would want to know their schizophrenia risk status. Participants anticipated schizophrenia risk would have a negative impact that was significantly greater than depression or diabetes risk but similar to cancer risk. The anticipated impact of schizophrenia risk was predicted by expectations of stigmatization as well as confidence in the accuracy of biological screening. Although 81% indicated a preference for knowing their risk status, just 11% were prepared to undergo an assessment to find out. In the second, a between-subjects deception paradigm was used to inform participants (n = 144 psychology undergraduates) they had an enzyme deficiency that placed them at increased risk for schizophrenia, cancer, or depression. Impact was assessed using prospective self-report and salivary cortisol and retrospective self-report. Impact was modeled using measures of stigmatization and health locus of control. Retrospectively, schizophrenia, cancer, and depression risk had strong negative impacts relative to a control group, but there was no effect on prospective measures. Together, the findings suggest that news of risk for schizophrenia has the potential to engender distress, although participants' anticipations and reflections of responses are not corroborated in prospectively measured outcomes.